Performance of a Rope Trawl in Deep Waters off North West Coast of India - S.V.S., Rama Rao; N., Subramonia Pillai; M.R., Boopendranath; M., Syed Abbas (Fishery Technology, 2025)
Design details of a newly developed 35 m rope trawl and the results of pre-feasibility trials conducted from FORV Sagar Sampada during November 1992 in the Exclusive Economic Zone off north west coast of India, are discussed in this paper. A total of 5.6 t of finfish and cephalopods were landed during the fifteen trial fishing operations realising an average catch rate of 396 kg hÂ· 1â€¢ The salient feature of the rope trawl is the substitution of netting in the fore part of the trawl by ropes thereby reducing the drag which results in fuel economy. The advantage of using rope trawl as a dual purpose trawl for both pelagic and demersal fishing is also discussed briefly.